Claiming the streets : processions and urban culture in South Wales, c. 1830-1880 - O'Leary, Paul (University of Wales Press, 2012)
Street processions were a defining feature of life in the Victorian town, and this book examines how those events created new civic identities in the growing towns of nineteenth-century south Wales.